1990
DOI: 10.1007/bf02244228
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-like activity of 5-HT1A agonists measured with the forced swim test

Abstract: This study examined the abilities of 5-hydroxytryptamine (5-HT) agonists with varying selectivity for different subtypes of 5-HT receptors to produce antidepressant-like behavioral effects in the forced swim test in rats. The 5-HT1A agonists 8-OH-DPAT (0.125-1.0 mg/kg, SC) and tandospirone (SM-3997) (5-20 mg/kg, SC) both produced dose-related decreases in immobility time following subchronic treatment in rats. These effects were similar to those of the tricyclic antidepressants imipramine (5-15 mg/kg) and desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
95
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(101 citation statements)
references
References 36 publications
5
95
0
1
Order By: Relevance
“…These data are compatible with the possibility that different receptors might be responsible for the antidepressant-like action of anpirtoline on the one hand and its antinociceptive effect and the ability to reverse isolation-induced social behaviour deficit on the other hand. Interestingly, the binding studies have shown that anpirtoline bound not only to (Wieland & Lucki, 1990;Martin et al, 1990;Martin & Puech, 1991), it might be tentatively proposed that the stimulation of central accounted for the antidepressant-like properties of anpirtoline. However, further studies are necessary to prove or reject this hypothesis.…”
Section: Discussionmentioning
confidence: 98%
“…These data are compatible with the possibility that different receptors might be responsible for the antidepressant-like action of anpirtoline on the one hand and its antinociceptive effect and the ability to reverse isolation-induced social behaviour deficit on the other hand. Interestingly, the binding studies have shown that anpirtoline bound not only to (Wieland & Lucki, 1990;Martin et al, 1990;Martin & Puech, 1991), it might be tentatively proposed that the stimulation of central accounted for the antidepressant-like properties of anpirtoline. However, further studies are necessary to prove or reject this hypothesis.…”
Section: Discussionmentioning
confidence: 98%
“…Although it is likely that a number of different 5-HT receptors may participate in the therapeutic effects of SSRIs, it is known that 5-HT 1A receptor agonists produce behavioral responses similar to those of established antidepressants (Wieland and Lucki 1990;Lucki et al 1994). However, the antidepressant-like action of 8-OH-DPAT was also reduced in WKY rats.…”
Section: Discussionmentioning
confidence: 99%
“…The study examined potential differences between strains in response to pharmacologically different types of antidepressant drugs; either the selective norepinephrine reuptake inhibitor desipramine or the selective serotonin reuptake inhibitor fluoxetine. In addition, the selective 5-HT 1A receptor agonist 8-hydroxy-2-(di-n-propylamino) tetralin (8-OH-DPAT; Wieland and Lucki 1990;Lucki et al 1994; was studied. The purpose of this study was to measure the different active behaviors emitted by the two rat strains at baseline in the FST, compare the response to noradrenergic and serotonergic drugs between rat strains, and determine whether distinctive active response components to antidepressants in the FST demonstrated previously in SD rats were maintained in the WKY strain.…”
mentioning
confidence: 99%
“…Further preclinical support for a central role for the 5-HTla receptor in MOD comes from the fact that 5-HTla agonists are effective antidepressants in animal models of depression such as learned help lessness and the forced swim test (Wieland and Lucki 1990;Cervo and Samanin 1987;Martin et al 1990). …”
mentioning
confidence: 99%